Monumental Propaganda - Ashton, Dore; Bitov, Andrei; Guidieri, Remo; Komar & Melamid; Licht, Fred Stephen; Young, James, E.; Zinik, Zinovy (New York : Independent Curators Incorporated, 1994)
Adams, Mac ; Aisenberg, Valeriy ; Andre, Carl ; Arhipov, Vladimir ; Arman, Armand ; Ast, Olga ; Avvakumou, Yuriy ; Beckmann, Robert ; Ben-Haim, Zigi ; Boym, Constantin ; Coyne, Petah ; Danilova, Irina ; etc.
Monumental Propaganda. A traveling exhibition organized and circulated by Independent Curators Incorporated, New York, 1994
boek
Keywords: Komar & Melamid